2005
DOI: 10.1902/jop.2005.76.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Promotes Cell Metabolism, Proliferation, and Osteoblastic Differentiation in Human Periodontal Ligament Cells

Abstract: These results suggest that at low concentration, simvastatin exhibits positive effect on proliferation and osteoblastic differentiation of human PDL cells, and these effects may be caused by the inhibition of the mevalonate pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 34 publications
7
69
1
5
Order By: Relevance
“…et al 6 stated the effect of SMV on human periodontal (PDL) cells in vitro and showed that, at a low concentration, SMV exhibits a positive effect on the proliferation and osteoblastic differentiation of human PDL cells, and these effects may be caused by inhibition of mevalonate pathway, indicating the role of SMV in bone regeneration. IL-6 and IL-8: In the present study, IL-6 and IL-8 levels are found to be higher in periodontitis patients, which is in accordance with studies done by Bartold et al 25 and Takahashi et al 26 This could be explained as Aggregatibacter actinomycetemcomitans and Campylobacter rectus have been shown to stimulate IL-6 and IL-8 production by human gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al 6 stated the effect of SMV on human periodontal (PDL) cells in vitro and showed that, at a low concentration, SMV exhibits a positive effect on the proliferation and osteoblastic differentiation of human PDL cells, and these effects may be caused by inhibition of mevalonate pathway, indicating the role of SMV in bone regeneration. IL-6 and IL-8: In the present study, IL-6 and IL-8 levels are found to be higher in periodontitis patients, which is in accordance with studies done by Bartold et al 25 and Takahashi et al 26 This could be explained as Aggregatibacter actinomycetemcomitans and Campylobacter rectus have been shown to stimulate IL-6 and IL-8 production by human gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Simvastatin (SMV), a synthetic statin, has a beneficial impact from a periodontal therapeutic standpoint on bone metabolism through osteoclast inactivation by affecting the generation of isoprenoids. 6 It has an anabolic effect and is a local stimulant for bone-growth regulatory factor. SMV also influences production of inflammatory cytokines via Creactive protein.…”
Section: Introductionmentioning
confidence: 99%
“…Cerivastatin was the most potent agent, while pravastatin was unable to stimulate BMP-2 promoter activity and new bone formation in neonatal murine calvaria (Garrett et al 2001b). Investigation of the effects of simvastatin on cell proliferation and osteoblastic differentiation in human periodontal ligament (PDL) cells showed that simvastatin enhanced cell proliferation and alkaline phosphatase activity in a dose-dependent fashion (Yazawa et al 2005). Maeda et al (2001) studied the effect of simvastatin on osteoblast differentiation and function using a nontransformed osteoblast (MC3T3-E1) cell line and rat bone marrow cells.…”
Section: In-vitro Studiesmentioning
confidence: 99%
“…Statins are specific inhibitors of 3-hydroxy-3methyl-glutaryl coenzyme A (HMGCoA) reductase and are some of the most used drugs in the treatment of atherosclerosis and other cardiovascular conditions [Pedersen et al 1996]. Recent in vitro research has indicated an anabolic effect of these drugs on bone [Yazawa et al 2005]. Moreover, simvastatin was found to enhance bone formation through induction of BMP-2 and alkaline phosphatase and by the accumulation of bone matrix proteins [Maeda et al 2001].…”
Section: The Current Status Of 'Old Drugs For New Applications'mentioning
confidence: 99%